When policy responses make things worse: The case of export restrictions on agricultural products - Laborde Debucquet, David; Mamun, Abdullah (Asian Development Bank, 2023)
We investigate two important questions based on an original data set on export restrictions placed on agricultural products developed at the International Food Policy Research Institute (IFPRI) and focus on three crises: the 2008 food price crisis, COVID-19, and the 2022 crisis linked to the Russian invasion of Ukraine. First, we analyzed in detail, using monthly trade data, the extent to which export restrictions disrupted normal trade patterns and affected importing countries. Second, although the justifications for these trade policies have been discussed in the literature, the possibility of forecasting their implementation remains understudied. However, understanding the drivers of such policies is key to avoid their implementation in the future. Analyses were conducted at a global level because agricultural markets are highly interconnected, especially for commodities, and policies in one part of the world could have drastic impacts on another region. We found that the least developed countries were those most affected by export restrictions. Countries in Asia are not immune to these restrictions because the region is home to many food-insecure countries. Countries in South Asia and Southeast Asia are most affected by the trade blockage of food staples. With regard to the prediction of export restriction, the econometric model used in our study suggested that domestic food prices have a higher predictive power than the world price of individual commodities. The same model applied to selected countries in Asia revealed the strong predictive power of food inflation for export restriction. Among the covariates studied, a country’s trade exposure and per capita income influence the imposition of export restrictions.